2018
DOI: 10.1089/sur.2017.264
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen- and Danger-Associated Molecular Patterns and the Cytokine Response in Sepsis

Abstract: The sepsis syndrome is a systemic host inflammatory response accompanied by organ dysfunction in response to invading microbial pathogens. The host recognizes both danger and pathogens through its pattern recognition receptors on immune cells. These receptors bind to pathogen- (PAMP) and danger- (DAMP) associated molecular patterns derived from microbes and host tissues, respectively. These processes set in motion a cascade of events in host cells and tissue, which activate multiple cytokines that serve as act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 86 publications
0
60
0
Order By: Relevance
“…This clinical condition can often progress to multi‐organ failure and is still a leading cause of mortality in the intensive care medicine (ICU) . Sepsis syndrome involves multiple pattern recognition receptors (PRRs) responding to pathogen‐associated molecular patterns (PAMPs), which synergize to activate innate and adaptive immunity, resulting in a complex pathophysiology process . Additionally, recent studies have verified that damage‐associated molecular patterns (DAMPs) released from host cells in response to pathogens can trigger immune response during sepsis …”
Section: Introductionmentioning
confidence: 99%
“…This clinical condition can often progress to multi‐organ failure and is still a leading cause of mortality in the intensive care medicine (ICU) . Sepsis syndrome involves multiple pattern recognition receptors (PRRs) responding to pathogen‐associated molecular patterns (PAMPs), which synergize to activate innate and adaptive immunity, resulting in a complex pathophysiology process . Additionally, recent studies have verified that damage‐associated molecular patterns (DAMPs) released from host cells in response to pathogens can trigger immune response during sepsis …”
Section: Introductionmentioning
confidence: 99%
“…More specifically, accumulating evidence reveals roles for that microRNAs (miRNAs) in various processes regulating inflammation regulation and immune responses, as these molecules inhibit the translation or degradation of mRNA to regulate the expressions of target genes [40]. The signaling cascade downstream of Toll-like receptors (TLRs) is a major pathway controlled by that miRNAs, such as miR-155, miR-125b, miR-223, let-7i, and let-7e [41]. Based on the investigation of miRNAs in sepsis [42].…”
Section: At the Genetic Level Genetic Testing Makes Facilitates The mentioning
confidence: 99%
“…IL-6 has been recognized as one of the most accurate biomarkers predictive of death in clinical sepsis. 3 The main pathogenic mechanism related to COVID-19 is the cytokine storm, characterized by massive release of pro-inflammatory cytokines and chemokines that characterize highly aggressive fatal forms. 2 Characteristic findings are leukopenia and lymphocytopenia.…”
Section: Referencesmentioning
confidence: 99%
“…The combined use of simulation-based education and digital technologies for dermatologic surgery has been previously reported. 3,4 Nicholas et al 5 carried out a pilot study and reported that learners were receptive to the use of simulators in their dermatologic training after a 2-day surgical symposium. More than 90% of the participants agreed that simulators were helpful.…”
Section: Dermatologic Surgery Training During the Covid-19 Eramentioning
confidence: 99%